2011
DOI: 10.1111/j.1365-2567.2011.03454.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-23 and T helper 17-type responses in intestinal inflammation: from cytokines to T-cell plasticity

Abstract: Summary Interleukin‐23 (IL‐23) plays an essential role in driving intestinal pathology in experimental models of both T‐cell‐dependent and innate colitis. Furthermore, genome‐wide association studies have identified several single‐nucleotide polymorphisms in the IL‐23 receptor (IL‐23R) gene that are associated with either susceptibility or resistance to inflammatory bowel disease in humans. Although initially found to support the expansion and maintenance of CD4+ T helper 17 (Th17) cells, IL‐23 is now recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 152 publications
(221 reference statements)
3
74
0
Order By: Relevance
“…Our finding that CD26 ++ IL-17-producing T cells are highly enriched in the inflamed tissues compared with the peripheral blood (Fig. 6C, 6D) is in agreement with previous studies implicating a role of Th17 cells in the pathogenesis of these inflammatory diseases (26,35), particularly inflammatory bowel disease (36). Interestingly, high levels of CD26 have previously been associated with autoimmune diseases, such as multiple sclerosis and rheumatoid arthritis (10,11).…”
Section: Discussionsupporting
confidence: 80%
“…Our finding that CD26 ++ IL-17-producing T cells are highly enriched in the inflamed tissues compared with the peripheral blood (Fig. 6C, 6D) is in agreement with previous studies implicating a role of Th17 cells in the pathogenesis of these inflammatory diseases (26,35), particularly inflammatory bowel disease (36). Interestingly, high levels of CD26 have previously been associated with autoimmune diseases, such as multiple sclerosis and rheumatoid arthritis (10,11).…”
Section: Discussionsupporting
confidence: 80%
“…With respect to the gastrointestinal tract, elevated levels of IL-17A, IL-17F, IL-21, and IL-22 have been found in both the inflamed intestine of humans with IBD and in experimental models of the disease. 8 Although IL-17A can promote proinflammatory responses through the induction of neutrophilattracting chemokines and matrix metalloproteinases, 9 we herein demonstrate that H. hepaticuseinduced typhlitis is exacerbated when IL-17A is neutralized, suggesting an anti-inflammatory role for this cytokine in T-celledriven bacteria-induced intestinal inflammation. Consistent with our findings, previous studies have reported exacerbation of dextran sulphate sodium colitis in the absence of IL-17A, through either antieIL-17A mAb treatment or the use of IL-17A À/À mice.…”
Section: Th17 Cytokines In H Hepaticus Colitismentioning
confidence: 87%
“…IL-23, which is crucial for driving both cecal and colonic inflammation in H. hepaticuseinfected hosts, 28 has multiple functions in the immune system, including promoting Th17-type cytokine secretion by T-and noneT-cell sources, inhibiting the differentiation of induced T-regulatory cells, and indirectly restraining IL-10 production by CD4 þ T cells. 8 As such, IL-23 may be an additional driver of pathology in the cecum that overrides the effect of IL-22 blockade. Although we did not find any difference in Il23a transcript levels between the cecum and colon, we observed enhanced mRNA levels of both Il12b and Il23r in the cecum compared with the colon, suggesting that the former tissue may be more responsive to IL-23.…”
Section: Th17 Cytokines In H Hepaticus Colitismentioning
confidence: 99%
See 2 more Smart Citations